KOMPETENSI KEPRIBADIAN GURU DALAM PERSPEKTIF IMAN KRISTEN BERDASARKAN KITAB GALATIA 5:22-23 - Pane, Pranada; Helminah, Helminah Yanti Simangunsong (UPPM Sekolah Tinggi Teologi Tabgha Batam, 2025)
Of course, competence in a teacher must be present, because this is an absolute requirement for him and also has the aim of providing knowledge and skills to students. Moreover, the knowledge provided must touch their cognitive, affective and psychomotor domains. Personality competency is also the main foundation for a teacher and is the capital for setting a good example. Personality competency also greatly influences the surrounding environment in which a teacher interacts and the influence exerted will produce a good impact. From a Christian perspective, of course it is very connected when a teacher's personality is linked to the truth of God's word. God's words in the book of Galatians explain how a believer must have the fruits of the Holy Spirit to change and equip his life so that he can give something good to others. This is no exception for a teacher, who of course must have the nine fruits of the Holy Spirit to make himself a better person. The more specific aim is that a teacher, apart from providing a good example, also provides knowledge of a spiritual or spiritual nature to provide a valuable value for his students because a teacher, especially a teacher who teaches Christian religious education subjects, is very closely related to spiritual matters.